PASAR SAYUR DAN IKAN PLAZA BERINGIN DI BUNTOK - Rif'an, Muhammad; Oktaviana, Anna (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
In Indonesia, markets are one of the biggest economic drivers for a region's income, and markets are also where buying and selling transactions take place. There are many necessities that people often buy at the market, including food necessities such as basic necessities, vegetables, fish and other staples. It is very important to pay attention to the related parties of the vegetable and fish market in Buntok City, where many parts of the construction are fragile and damaged, and also the condition of this market is chaotic, where the road for visitor circulation is converted into a parking lot and a place for merchandise, which makes market users uncomfortable because user access is narrow due to lack of arrangement by the related parties. Based on the facts behind the design of the Plaza Beringin vegetable and fish market in Buntok, the question is